Influence On Thrust Force And Delamination For One Shot Drilling Of Carbon Fibre Reinforced Plastic (CFRP) - Salleh, Mohd Shukor; Jaafar, Mohd Fairuz; Raja Abdullah, Raja Izamshah; Hassan, Muhammad Hafiz; Sundi, Syahrul Azwan; Mohd Shahrim, Mohammad Shah All Hafiz; Kasim, Mohd Shahir (International Journals Of Engineering And Sciences Publisher (IJENS), 2019)
The requirement of drilling process of Carbon Fibre Reinforced Plastic (CFRP) is vital in order to fulfil final assembly specifications. Despite the excellent mechanical properties of composites, they are hard to be machined due to its toughness. The damages such as peel-up and push-out delamination usually occur during its machining. To provide drilling induced delamination is a priority to reduce parts rejection and lead to waste in time and money. In this work, a comparative study of three geometries under different cutting conditions is presented. Application Taguchi’s design of experiments for this experimental works increase the analysis reliability. Various penetration angle drilling also studied to determine the effect of thrust force and delamination. Thrust force was monitored during drilling tests, and delamination extension was quantified using image processing software. Results are processed using analysis of variance (ANOVA) then further presented by response surface graph showed that the best drill geometry, spindle speed and feed rate selection is fundamental to reduce delamination. The result obtained from the analysis shown delamination both for peel-up and push-out spread worse with increasing of drilling angle. Delamination factors are directly proportional with thrust force generated during drilling and increasing of thrust force will worsening the delamination damages. Straight flute drill is the best drill that generates lower thrust force thus reducing delamination effect compared with twist and dagger drill which on optimum feed rate and spindle speed parameter is 0.05 mm/rev and 4000 rpm, respectively.